Роль та значення митного контролю як інструменту протидії тіньовій економіці - Рябчук, Оксана Григорівна; Салямон-Міхєєва, Катерина Дмитрівна; Оксана, Рябчук (Державний податковий університет, 2023)
Стаття присвячена обґрунтуванню вирішальної ролі та значення митного контролю у боротьбі з тіньовою економікою та підтримці фінансового добробуту держави. Встановлено, що зростання рівня тіньової економіки свідчить про недостатню ефективність та результативність митного контролю, що пов’язано з низкою проблем української митниці, таких як корупція, тривалість митних процедур, підробка документів, значні транспортні та часові витрати на оформлення товарів у суміжних службах, залежність митної служби від політичного впливу, непрозорість у призначенні посадових осіб митних органів, недостатня кваліфікація митників. Для вирішення зазначених проблем та підвищення ефективності механізмів митного контролю запропоновано уніфікувати митний тариф, інтегрувати митну систему з системами інших державних органів, підприємств та установ, здійснити комплексну діджиталізацію, автоматизацію прийняття рішень, розвивати людські ресурси.

The article is devoted to the definition of the key role and importance of customs control in solving problems associated with the shadow economy. The relevance of the study is due to the urgent need for effective measures to combat the shadow economy in Ukraine, where it poses a significant threat to the fiscal system, economic growth and social welfare. As Ukraine continues to advance on the path of economic reform and European integration, understanding the critical role of customs control is of particular importance. Purpose. The article is aimed at developing solutions aimed at improving the efficiency of customs control mechanisms to counter the shadow economy and ensure sustainable economic development of the state. Methods. In the course of the study, general scientific methods of cognition were used: critical analysis, synthesis of information, induction and deduction. Results. The study found that customs control is important in the fight against the shadow economy and ensuring the financial health of the state. However, the growth of the shadow economy indicates that customs control is insufficiently effective and efficient. This is due to a number of problems of the Ukrainian customs, such as corruption, duration of customs procedures, forgery of documents, significant transport and time costs for registration of goods in related services, dependence of the customs service on political influence, lack of transparency in the appointment of customs officials, insufficient qualification of customs officers. Conclusion. Customs control plays a crucial role in combating the shadow economy and supporting the financial well-being of the state. Nevertheless, the growing prevalence of the shadow economy indicates the lack of effectiveness of existing customs control measures to achieve optimal performance. To solve these problems and increase the efficiency of customs control mechanisms, it is proposed to unify the customs tariff, integrate the customs system with the systems of other state bodies, enterprises and institutions, comprehensive digitalization, automation of decision-making, development of human resources. The practical significance of the study lies in the possibility of using the results obtained by state authorities to improve the customs control system in Ukraine, which will reduce the level of the shadow economy, improve the financial stability of the state and its economic development.
Keywords: митний контроль; тіньова економіка; пост-митний контроль; митний аудит; інструмент протидії; customs control; shadow economy; post-customs control; customs audit; countermeasure tool